Kehidupan Sosial Ekonomi Industri Rumah Tangga Gula Enau (Aren) Di Nagari Andaleh Baruh Bukik Kecamatan Sungayang Kabupaten Tanah Datar (1998-2020) - Alya Yukha Winona; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2022)
Abstract This study is a study on the Socio-Economic Life of The Sugar Enau Household Industry (Aren) located in Nagari Andaleh Baruh Bukik Sungayang District, Tanah Datar Regency in 1998-2020. The purpose of this study is to find out the expansion of the enau (aren) sugar household industry in Nagari Andaleh Baruh Bukik in 1998-2020, and the impact of the production of the enau (aren) sugar household industry in Nagari Andaleh Baruh Bukik in 1998-2020. This research is a study that uses historical methods with four stages of research methods, namely: heuristics, source criticism, interpretation, and historiography. Based on the results of research, it can be known that the socio-economic life of the sugar enau (aren) household industry in Nagari Andaleh Baruh Bukik in 1998-2020 experienced a significant development, it can be seen from the price, production and value of sugar enau (aren) from 1998-2020 experienced a link and a decrease of one of them was caused by the issue of sugar enau (aren) oplosan. And in 2020 the existence of the enau (aren) sugar household industry in Nagari Andaleh Baruh Bukik has carried out P-IRT permits and production brand distribution. Keywords: Enau Sugar Household Industry (Aren), Development, Socio-Economic